Surface Cooling Causes Accelerated Degradation Compared to Tab Cooling for Lithium-Ion Pouch Cells. Issue 9 (1st January 2016) - Hunt, Ian A.; Zhao, Yan; Patel, Yatish; Offer, G. J.
Abstract : One of the biggest causes of degradation in lithium-ion batteries is elevated temperature. In this study we explored the effects of cell surface cooling and cell tab cooling, reproducing two typical cooling systems that are used in real-world battery packs. For new cells using slow-rate standardized testing, very little difference in capacity was seen. However, at higher rates, discharging the cell in just 10 minutes, surface cooling led to a loss of useable capacity of 9.2% compared to 1.2% for cell tab cooling. After cycling the cells for 1, 000 times, surface cooling resulted in a rate of loss of useable capacity under load three times higher than cell tab cooling. We show that this is due to thermal gradients being perpendicular to the layers for surface cooling leading to higher local currents and faster degradation, but in-plane with the layers for tab cooling leading to more homogenous behavior. Understanding how thermal management systems interact with the operation of batteries is therefore critical in extending their performance. For automotive applications where 80% capacity is considered end-of-life, using tab cooling rather than surface cooling would therefore be equivalent to extending the lifetime of a pack by 3 times, or reducing the lifetime cost by 66%.